The role of urban food policy in preventing diet-related non-communicable diseases in Cape Town and New York. Issue 4 (April 2015) - Libman, K.; Freudenberg, N.; Sanders, D.; Puoane, T.; Tsolekile, L.
Abstract Objectives Cities are important settings for production and prevention of non-communicable diseases. This article proposes a conceptual framework for identification of opportunities to prevent diet-related non-communicable diseases in cities. It compares two cities, Cape Town in South Africa and New York City in the United States, to illustrate municipal, regional, national and global influences in three policy domains that influence NCDs: product formulation, shaping retail environments and institutional food practices, domains in which each city has taken action. Study design Comparative case study. Methods Critical analysis of selected published studies and government and non-governmental reports on food policies and systems in Cape Town and New York City. Results While Cape Town and New York City differ in governance, history and culture, both have food systems that make unhealthy food more available in low-income than higher income neighborhoods; cope with food environments in which unhealthy food is increasingly ubiquitous; and have political economies dominated by business and financial sectors. New York City has more authority and resources to take on local influences on food environments but neither city has made progress in addressing deeper social determinants of diet-related NCDs including income inequality, child poverty and the disproportionate political influence of wealthy elites. Conclusions Through their intimate connections with the daily lives of their residents, municipal governments have the potential to shape environments that promote health. Identifying the specific opportunities to prevent diet-related NCDs in a particular city requires intersectoral and multilevel analyses of the full range of influences on food environments.